Grainsize analysis and radionuclide measurements (210Pb, 137Cs, 226Ra) obtained from sediment cores RD04 (island of Sylt), BT02 and BT03 (Eiderstedt peninsula; south-eastern North Sea) - Nina Lenz; Sebastian Lindhorst (PANGAEA, 2021)
Three sediment cores were retrieved from marshes at the southern North Sea coast, recovering the past 100 years. Core RD04 originates from a natural back-barrier marsh (island of Sylt); cores BT02 and BT03 from a reinstated, former managed marsh (Eiderstedt peninsula). Whereas the marsh in Sylt is a low-energy, back-barrier marsh, the marsh in Eiderstedt is exposed to storm waves from the open North Sea. The study provides a characterisation of the sedimentary processes that control vertical salt marsh growth in different energetic settings. Data include grain-size analysis and radionuclide activity of 137-Cs, 210-Pb and 226-Ra. Measurements of the radionuclides were used to determine sediment accretion rates. Grain-size data were used to determine and quantify multiple sedimentary processes by the application of end-member modelling.